Percutaneous Mitral Valve Repair versus Optimal Medical Therapy in Patients with Functional Mitral Regurgitation: A Systematic Review and Meta-Analysis - Muhammad Uzair Lodhi; Muhammad Shariq Usman; Tariq Jamal Siddiqi; Muhammad Shahzeb Khan; Muhammad Arbaz Arshad Khan; Safi U. Khan; Intekhab Askari Syed; Mustafa Rahim; Srihari S. Naidu; Rami Doukky; Mohamad Alkhouli (Journal of Interventional Cardiology)
Objectives. To compare percutaneous mitral valve repair (PMVR) with optimal medical therapy (OMT) in patients with heart failure (HF) and severe functional mitral regurgitation (FMR). Background. Many patients with HF and FMR are not suitable for surgical valve replacement and remain symptomatic despite maximal OMT. PMVR has recently emerged as an alternative solution. Methods. We performed a systematic review and a meta-analysis to address this question. Cochrane CENTRAL, MEDLINE, and Scopus were searched for randomized (RCT) and nonrandomized studies comparing PMVR with OMT in patients with HF and FMR. Primary endpoint was all-cause midterm mortality (at 1 and 2 years). Secondary endpoints were 30-day mortality and cardiovascular mortality and HF hospitalizations, at maximum follow-up. Studies including mixed cohort of degenerative and functional MR were allowed initially but were excluded in a secondary sensitivity analysis for each of the study’s end points. This meta-analysis was performed following the publication of two RCTs (MITRA-FR and COAPT). Results. Eight studies (six observational, two RCTs) comprising 3,009 patients were included in the meta-analysis. In comparison with OMT, PMVR significantly reduced 1-year mortality (RR: 0.70 [0.56, 0.87]; p=0.002; I2=47.6%), 2-year mortality (RR: 0.63 [0.55, 0.73]; p<0.001; I2=0%), and cardiovascular mortality (RR: 0.32 [0.23, 0.44]; p<0.001; I2=0%). No significant difference between PMVR+OMT and OMT was noted in HF hospitalization (HR: 0.69 [0.40, 1.20]; p=0.19; I2=85%) and 30-day mortality (RR: 1.13 [0.68, 1.87]; p=0.16; I2=0%). Conclusions. In comparison with OMT, PMVR significantly reduces 1-year mortality, 2-year mortality, and cardiovascular mortality in patients with HF and severe MR.